IMPLEMENTASI PEMBERIAN TUGAS SEBELUM PROSES PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR FISIKA MATERI HUKUM NEWTON PADA SISWA SMK - Haning Hasbiyati (FKIP Universitas Islam Jember, 2015)
Based on the analysis of problems in SMK 1 Lumajang , researchers acknowledged that it was necessary to make an innovations in Teaching-learning physics. By giving the task before learning materials Newton's Law was expected to increase students’ motivation and their learning outcomes. The purpose of this study was (1) to investigate the ability of vocational high school students by giving the task before the learning process on Newton's Law matter, (2) to know the attitude of vocational high school students by giving the task before the learning process on Newton's Laws material and determine the skills of vocational students by giving the task before the learning process on Newton's Laws material.This study was conducted at SMK Negeri 1 Lumajang . The subjects were the 38 students of class X TKI 4. This research was conducted in the 1st half of the school year 2014-2015 . This research was a classroom action research that consisted repeated cycle; planning, implementing, reflecting the collaborative action and participation.The findings showed good improvement, in the first cycle there were no students who could achieve an